(untitled) (GIST – Education and Learning Research Journal, 2020)
In the last few decades, several studies have documented the discrimination that teachers face in the field of Teaching English for Speakers of Other Languages (TESOL). To date, research evidence has shown that discrimination tends to be motivated by issues concerning the native- vers. non-native language status of these professionals. However, recent evidence has suggested that discrimination in TESOL is intricate involving factors that are associated with the language status of teachers, their pronunciation, gender, race, sexual preference, age, among others. Despite the fact that this evidence has revealed the struggles of these professionals, no research discourse, to my knowledge, has shown the extent to which these phenomena impact on the professionals’ perceptions, feelings and decision making. In response to this, the present study was conducted to understand the effects and results of discrimination in the field of TESOL in Mexico from the professionals’ perspectives. Through an online questionnaire, 78 Mexican English as a foreign language (EFL) teachers were asked to describe the instances in which they felt discriminated, and how these influenced their perceptions and decision making concerning their profession. The results show that the discrimination practices impact in complex ways, showing negative effects on the professionals’ perceptions, feelings and decisions regarding their current profession. This evidence calls for more effective strategies in order to stop affecting teachers in ELT.